Perlindungan Hukum terhadap Nasabah terkait Bocornya Data Nasabah berdasarkan Perspektif Hukum Perbankan - Gusti Putu Krisna Bhagaskara; I Made Dedy Priyanto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The purpose of this study is to examine the role of bank secrets in carrying out their duties as protection against leaking customer data. This study uses normative legal research methods with a statutory and comparative approach. The results showed that bank secrets provide protection against leakage of banking customer data, but there is expected to be additional sansk for lawbreakers leaking bank secrets in the future